Vietnamese American women's beliefs and perceptions on cervical cancer, cervical cancer screening, and cancer prevention vaccines: A community-based participatory study - Connie Kim Yen Nguyen-Truong; Kim Quy Vo Nguyen; Thai Hien Nguyen; Tuong Vy Le; Anthony My Truong; Keara Rodela; Rachael Allan (JMIR Publications, 2017)
Cervical cancer remains commonly diagnosed in Vietnamese American women. Despite efforts to increase cervical cancer screening among Vietnamese American women, participation rates are persistently lower than the national goal. The objective of this study is to explore beliefs of Vietnamese American women about cervical cancer, cervical cancer screening, and cancer prevention vaccines. A qualitative descriptive investigation captured group perceptions about meaning and beliefs of cervical cancer, screening, and cancer prevention vaccines, and participants' stories using a community-based participatory research approach. Forty Vietnamese American women were recruited from the Portland, Oregon metropolitan area into four focus groups. Using a process of directed content analysis, focus group transcripts were coded for themes. We found that cervical cancer continues to be a difficult topic to discuss, and Vietnamese American women may not bring the topic up themselves to their health care providers. Some women experienced intense emotions of fear or shame of having their cervix examined. Women delayed seeking cervical cancer screening and needed to have early warning signs, which guided them as to when to seek health care. Women focused on cleanliness through vaginal and/or perineal washing as primary prevention for cervical cancer. There were limited awareness and knowledge about cancer prevention vaccines, specifically the human papillomavirus. Some women relied heavily on their informal social networks of family, friends, or community for health knowledge. Fear and misunderstanding dominated the beliefs of Vietnamese American women about cervical cancer screening and prevention. These findings underscored the importance of having culturally-specific findings, which will inform a multicomponent intervention to promote cervical cancer screening and cancer prevention vaccine uptake within this population.